A review of health system infection control measures in developing countries: what can be learned to reduce maternal mortality - Sharma Sheetal; Mavalankar Dileep V; Hussein Julia; D'Ambruoso Lucia (BMC, 2011)
Abstract A functional health system is a necessary part of efforts to achieve maternal mortality reduction in developing countries. Puerperal sepsis is an infection contracted during childbirth and one of the commonest causes of maternal mortality in developing countries, despite the discovery of antibiotics over eighty years ago. Infections can be contracted during childbirth either in the community or in health facilities. Some developing countries have recently experienced increased use of health facilities for labour and delivery care and there is a possibility that this trend could lead to rising rates of puerperal sepsis. Drug and technological developments need to be combined with effective health system interventions to reduce infections, including puerperal sepsis. This article reviews health system infection control measures pertinent to labour and delivery units in developing country health facilities. Organisational improvements, training, surveillance and continuous quality improvement initiatives, used alone or in combination have been shown to decrease infection rates in some clinical settings. There is limited evidence available on effective infection control measures during labour and delivery and from low resource settings. A health systems approach is necessary to reduce maternal mortality and the occurrence of infections resulting from childbirth. Organisational and behavioural change underpins the success of infection control interventions. A global, targeted initiative could raise awareness of the need for improved infection control measures during childbirth.